ANALYSIS OF COFFEE SHOP ENVIRONMENTAL FACTORS IN ENCOURAGING LEARNING CREATIVITY: ANALISIS FAKTOR-FAKTOR LINGKUNGAN COFFEE SHOP DALAM MENDORONG KREATIVITAS BELAJAR - Azam Yusbyakto; Harianto; Bambang Martin Baru (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to analyze the environmental factors of coffee shops that contribute to enhancing students’ learning creativity in Madiun City, particularly at the Kopi Dari Hati coffee shop. In the modern era, coffee shops are not only places for leisure but have evolved into alternative spaces for students to study and express creativity. A comfortable, aesthetic, and flexible environment is believed to influence mood, motivation, and creative thinking during learning activities. This research employs a descriptive qualitative approach through field observation, interviews, and documentation. The informants consist of the owner, employees, and student visitors of the coffee shop. The findings reveal that physical factors such as spatial layout, interior design, and lighting have significant effects on comfort and concentration during study activities. Meanwhile, social factors such as visitor interactions and the level of social comfort also contribute to creating an inspiring and stress-free learning atmosphere. Flexible room arrangements, aesthetic interiors, warm lighting, and the presence of both quiet and lively zones are identified as dominant elements that support the emergence of creative ideas. However, minor obstacles such as limited power outlets, noise, and small table sizes remain challenges for some visitors. Overall, the study concludes that coffee shops can serve as effective alternative learning spaces when they successfully balance functional, aesthetic, and social aspects to facilitate students’ creative learning processes.